2023
DOI: 10.3390/ijerph20021241
|View full text |Cite
|
Sign up to set email alerts
|

Linking Cognitive Reappraisal and Expressive Suppression to Mindfulness: A Three-Level Meta-Analysis

Abstract: Cognitive reappraisal and expressive suppression have long been considered the two most important emotion regulation strategies. Increasingly, studies have found that mindfulness has a relationship with them. However, the magnitude and direction of the relationship between them have yet to reach a consistent conclusion. To this end, a three-level meta-analysis was used to explore the relationship between mindfulness, cognitive reappraisal, and expressive suppression. Thirty-six studies were included in the met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 70 publications
(81 reference statements)
0
2
0
Order By: Relevance
“…In the present study, we focus on two widely studied emotion regulation strategies: expressive suppression and cognitive reappraisal. Previous studies have shown that the two emotion regulation strategies operate in contrasting effects ( Zhou et al, 2023 ), and differ in terms of psychological processes and physiological mechanisms ( Bebko et al, 2011 ; Hermann et al, 2014 ). Considering with these findings and referencing relevant literature ( Zhang et al, 2023 ), the present study explored the mediating effect of cognitive reappraisal and/or expressive suppression, respectively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the present study, we focus on two widely studied emotion regulation strategies: expressive suppression and cognitive reappraisal. Previous studies have shown that the two emotion regulation strategies operate in contrasting effects ( Zhou et al, 2023 ), and differ in terms of psychological processes and physiological mechanisms ( Bebko et al, 2011 ; Hermann et al, 2014 ). Considering with these findings and referencing relevant literature ( Zhang et al, 2023 ), the present study explored the mediating effect of cognitive reappraisal and/or expressive suppression, respectively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study further emphasizes the importance of increasing the use of cognitive reappraisal and reducing the utilization of expressive suppression as an emotion regulation strategy in coping with stressors associated with polycystic ovary syndrome. Previous studies have provided evidence that mindfulness (Zhou et al, 2023), cognitive-behavioral therapy (CBT) (Dryman and Heimberg, 2018) are effective in enhancing cognitive reappraisal, and exposure therapy is effective in reducing expressive suppression (Dryman and Heimberg, 2018). Therefore, therapists should incorporate CBT directly and repeated cognitive restructuring exercises and exposure therapy into intervention programs aimed at improving the mental health of women with PCOS.…”
Section: Discussionmentioning
confidence: 99%